The Study Of The Adoption Level Of Wireless Local Area Network (WLAN) By Companies In Cyberjaya Malaysia - Vooi, Chang Voon (2004)
Currently there are over 136 companies operated in Cyberjaya. So far there is not much research has been carried out to study the adoption level of wireless LAN. There are some factors that will affect companies in adopting wireless LAN technology.